INFLUENCE OF THE COMPOUND SS-68 ON THE ELECTROPHYSIOLOGICAL EFFECTS OF ADRENOMIMETICS IN RAT RIGHT ATRIUM - S. K. BOGUS; D. V. ABRAMOCHKIN; A. V. ZELENSKAYA; K. F. SUZDALEV; P. A. GALENKO-YAROSHEVSKY (Кубанский научный медицинский вестник, 2017)
The influence of compound SS-68, known for its marked antiarrhythmic properties, on the intension of electrophysiological effects of α1- и β- adrenoreceptors stimulation was studied in right atrial preparations from rat. Activation of α1-adrenoreceptors by methoxamine (3×10-5М) led to prominent prolongation of action potentials without significant changes in their rhythm. SS-68 attenuated this effect with IC50 = 5,27×10-6М. The standard α1-blocker prazosine appeared to be more effective (IC50 = 2×10-7М). The activation of β-adrenoreceptors by isoproterenol (3×10-7М) led to drastic acceleration of sinus rhythm. However, only the highest tested concentration of SS-68 (3×10-5М) reduced this effect, while the conventional β-blocker atenolol effectively inhibited it with IC50 = 3,95×10-6М.